Mobile Hazard Inspection Robot - Ahmad Afnan bin Yusof, Ahmad Afnan (2010)
This project aims to create a cheap, working prototype of a mobile, autonomous robot capable of patrolling and inspecting hazardous high-risk places for any fires. In this study, research and experimental work were carried out to see if the Wiimote would make an excellent device for fire detection for use in routine maintenance checks, apart from design of mobile robot that uses affordable materials and also the robot’s patrolling capability.